Low Fetal Fraction and Birth Weight in Women with Negative First-Trimester Cell-Free DNA Screening - Clapp, Mark A.; Berry, Margaret; Shook, Lydia L.; Roberts, Penelope S.; Goldfarb, Ilona T.; Bernstein, Sarah N. (American Journal of Perinatology, 2020)
Objective To determine the association between low fetal fraction and birth weight among women with a negative cell-free DNA (cfDNA) result for common aneuploidies in the first trimester.Study Design This is a retrospective cohort of women who delivered a singleton between July 2016 and June 2018 at a single institution and had normal cfDNA testing in the first trimester. The primary variable of interest was “low fetal fraction,” which was defined as fetal fractions less than 5th percentile among all fetal fractions in the cohort (fetal fraction < 5.34%). The primary outcomes were birth weight ≤ 5th and ≤ 10th percentiles. Multivariable logistic regressions assessed for the association between low fetal fraction and birth weight.Results A total of 7,478 women delivered a singleton at ≥24 weeks' gestation, of which 2,387 (32%) underwent genetic screening through cfDNA; the majority were in the first trimester (n = 2,052 [86%]). 2,035 met the inclusion criteria. Birth weight ≤ 5th percentile was significantly higher in the low fetal fraction group (6.9 vs. 3.2%; p = 0.04). A low fetal fraction was associated with higher odds of an infant with a low birth weight: adjusted odds ratio (aOR) of 2.32 (95% CI 1.15–4.67) for birth weight ≤ 10th percentile (p = 0.02) and aOR of 3.73 (95% CI 1.40–9.03) for birth weight ≤ 5th percentile (p = 0.004).Conclusion Low fetal fractions of ≤ 5th percentile were associated with an increased risk of birth weights ≤ 5th and ≤ 10th percentiles in women with negative cfDNA screening in the first trimester. Future work is needed to further investigate this relationship and to determine the potential clinical implications, such as third-trimester screening for growth restriction in women with low fetal fractions and negative cfDNA screening results.
Keywords: genetic screening; cell-free DNA; aneuploidy; low birth weight; intrauterine growth restriction